The lure of Pokemon video games and the savage mind - Nakazawa, Shin'ichi 1950- (Japan Bunka Sangyo? Shinko? Zaidan))
From its humble beginnings as a video game launched in the mid-90s, Pokemon has become a global entertainment franchise, even reaching into the world via "augmented reality" with the mobile game Pokemon GO. In the work, Nakazawa Shinichi argues that the Pokemon worldview is the best contemporary example of Claude Le?vi-Strauss's "savage mind" (la pense?e sauvage), suggesting that computer games can often be viewed as attempts to reconnect the human unconscious with the true, hidden essence of nature. --Publisher Space Invaders revolution -- The birth of monsters -- Eros, Thanatos, and RPGs -- The triumphs of Pokemon -- Totemism today -- The Gift and the world of gaming -- Epilogue --Afterword to the first edition (1997) -- Appendices. Pokemon GO, or, the dream of the good walker -- The game freaks who play with bugs -- The origins of Pokemon / by Satoshi Tajiri.